UPAYA MOTIVASI DAN AKTIVITAS BELAJAR IPA PADA MATERI PENGUKURAN DENGAN MENGGUNAKAN MEDIA ANIMASI FLASH DI SMP NEGERI 3 PERCUT SEI TUAN - Untung Narpati (Universitas Negeri Medan, 2013)
This research is aimed to find out the efforts to raise students’motivation and learning activity by utilizing flash animation media on the Science subject on the topic discussion of “Pengukuran” to the seventh gradestudents of SMP Negeri 3 Percut Sei Tuan. The subjects of the research werethirty students of seventh grade Academic Year 2012/2013 that consist of 15males and 15 females. The object of the research was how to raise thestudents’ motivation and learning activity by utilizing flash animation mediabased on the STAD theory. The result reveals that: (1) there is an averagerise of the students’ learning completeness which is indicated by (a) the test result in the first stage completes 63.33%, (b) the test-result in the secondstage completes 86.70% and the index gain is 0.32% which raises mediumcriteria. (2) Students learning activity is found rose which is indicated by theincreasing average percentage of 72.40 in the first stage becomes 88.48 inthe second stage. (3) There is an increasing number of students learningmotivation which is known that students’ motivation in the attentioncondition rises as much as 28.44% from 52.89% in the first stage becomes81.33% in the second stage, there is an increasing number in the relevancecondition as much as 23.67% from 64.75% in the first stage becomes88.42% in the second stage, there is an increasing number in the confidencecondition as much as 30.86% from 57.71% in the first stage become 88.57%in the second stage, on the satisfaction condition; there is also increasingnumber as much as 23.58% from 65.33% in the first stage becomes 88.92%in the second stage.